A sensitive procedure to determine o-cresol using multicommutation and a portable photometer with a long optical pathway cell - Ródenas Torralba, Eva; Reis, Boaventura; Morales Rubio íngel; de la Guardia, Miguel (Ciencia)
A fast and sensitive procedure was developed for determining o-cresol in water samples, by using a homemade light emitting diode (LED)-based photometer (ï¬= 590 nm), a 10 cm optical pathway cell and the micro-pumping strategy. The method is based on the measurement of the formation of o-cresol derivate with 100 mg/L p-aminophenol (PAP) and 0.004 mol/L KIO4 in presence of NaOH 0.06 mol/L. Two different methodologies have been compared; (i) batch analysis in a conventional spectrophotometer using an optical pathway cell of 1 cm, (ii) multicommuted flow injection procedure and a portable LED-based photometer (25 cm x 22 cm x 10 cm, 3 Kg) with a 10 cm cell length. O-cresol reaction requires ca. 17 min for the full development of the colour with PAP. Nevertheless, the developed procedure was carried out in the stopped-flow mode using a reaction time of 3 min. Good results were obtained and the calibration equation was I = (170 ± 5) Co-cresol + (0 ± 9) with R = 0.9993. Limits of detection of 10 and 80 ng/mL and repeatability of 2.8 and 1.9 % relative standard deviation were obtained for the 10 cm cell and for the conventional 1 cm cell, respectively. Multicommutation, using a long pathway cell (10 cm), has shown a higher sensitivity, but it only permitted a maximum of 20 determinations per hour, as low as batch procedure. o-Cresol can be determined in water samples and recoveries from 92 to 105 % were found in spiked tap, waste and irrigation waters. The paired Student’s t test compared with batch data was lower than the theoretical t value (2.306) for a 95% probability level and 8 degrees of freedom.